TARAWANGSA DAN JENTRENG DALAM UPACARA NGALAKSA DI RANCAKALONG SUMEDANG JAWA BARAT (Sebagai Sarana Komunikasi Warga) - Ela Yulaeliah (SELONDING, 2006)
Ngalaksa ceremony is an expression of thankfulness to the God for His gift allowing the the rice harvest. The ceremony is conducted by six villagers in district Rancakalong Sumedang regency and lasts six days and nights with the accompaniment of tarawangsa and jentreng music played countinously. This ceremony is held once in a year following the rice harvest and at the same time regarded as the preparation of the next plant season. Apart from the thankfulness expression, ngalaksa is also considered as an honour of people toward Dewi Sri (the rice Goddess) and as a meeting and communicating arena of the people. Ngalaksa is commenced with the making of laksa (a kind of porrage made of the rice flour, wrapped with congkok leaves {a sort of leaves similar to coconut leaves}, which have been steamed before). The certain people believe that if the number of laksa packages is more than those in the last year, the result of harvest in the next year would be better. There are usually hundreds o/laksa distributed to all participants of the ceremony. The process of making laksa spends four to five days. In the seventh day, regarded as the ultimate days, there is an activity to get the rice into the barn (lumbung) as a symbol of getting rice back to the higher place. At that time, the participants dance with spontaneous movement that is accompanied with tarawangsa am/jentreng music. They are sure that at the time, ancestor spirits including Dewi Sri get down to the earth and dance together with them.